Prevalence and risk factors for acute stress disorder in female victims of sexual assault. (December 2021) - Garcia-Esteve, Ll.; Torres-Gimenez, A.; Canto, M.; Roca-Lecumberri, A.; Roda, E.; Velasco, ER.; Echevarría, T.; Andero, R.; Subirà, S.
Highlights: Female victims of sexual assault have a high predisposition to develop acute stress disorder. Nationality, psychiatric history, peritraumatic dissociation and type of assault are risk factors associated to acute stress disorder. The risk factors can be used in the emergency department to detect vulnerable victims that require early interventions. Abstract: Sexual assault is one of the most traumatic events a person can experience. Despite this, information regarding the risk factors associated with the development of Acute Stress Disorder (ASD) in sexual assault victims is scarce. A follow-up prospective cohort study was designed to examine the prevalence and risk factors of ASD in women exposed to a recent sexual assault. A total of 156 women were treated at the Emergency Department of a university general hospital shortly after sexual assault. Sociodemographic, clinical and sexual assault-related variables were collected. The Acute Stress Disorder Interview was used to estimate the prevalence of ASD at three weeks post-SA. From the 156 victims, 66.6% ( N = 104) met ASD diagnosis using DSM-5 criteria, whereas 59.6% ( N = 93) met ASD diagnosis using DSM-IV criteria. The risk factors associated with the development of ASD were nationality, psychiatric history, peritraumatic dissociation and type of assault. In conclusion, the prevalence of ASD in female victims of recent sexual assault was high, affecting approximately two thirds of them. The recognition of the risk factors associated with ASD development, like peritraumatic dissociation or type of assault, may aid in the prompt detection of vulnerable women that require early and specific interventions shortly after trauma.